The Use of Evidence-Based, Problem-Oriented Templates as a Clinical Decision Support in an Inpatient Electronic Health Record System - Mehta, Raj; Radhakrishnan, Nila S.; Warring, Carrie D.; Jain, Ankur; Fuentes, Jorge; Dolganiuc, Angela; Lourdes, Laura S.; Busigin, John; Leverence, Robert R. (Applied Clinical Informatics, 2016)
The integration of clinical decision support (CDS) in documentation practices remains limited due to obstacles in provider workflows and design restrictions in electronic health records (EHRs). The use of electronic problem-oriented templates (POTs) as a CDS has been previously discussed but not widely studied.We evaluated the voluntary use of evidence-based POTs as a CDS on documentation practices.This was a randomized cohort (before and after) study of Hospitalist Attendings in an Academic Medical Center using EPIC EHRs. Primary Outcome measurement was note quality, assessed by the 9-item Physician Documentation Quality Instrument (PDQI-9). Secondary Outcome measurement was physician efficiency, assessed by the total charting time per note.Use of POTs increased the quality of note documentation [score 37.5 vs. 39.0, P = 0.0020]. The benefits of POTs scaled with use; the greatest improvement in note quality was found in notes using three or more POTs [score 40.2, P = 0.0262]. There was no significant difference in total charting time [30 minutes vs. 27 minutes, P = 0.42].Use of evidence-based and problem-oriented templates is associated with improved note quality without significant change in total charting time. It can be used as an effective CDS during note documentation.Citation: Mehta R, Radhakrishnan NS, Warring CD, Jain A, Fuentes J, Dolganiuc A, Lourdes LS, Busigin J, Leverence RR. The use of evidence-based, problemoriented templates as a clinical decision support in an inpatient electronic health record system.
Keywords: Clinical information systems; electronic health records and systems; clinical decision support; clinical documentation and communications; encounter notes; inpatient care